2018
DOI: 10.1017/s0022149x18000834
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the newly invasive New Guinea flatworm Platydemus manokwari (Platyhelminthes: Geoplanidae) in Thailand and its potential role as a paratenic host carrying Angiostrongylus malaysiensis larvae

Abstract: Invasive species constitute one of the most serious threats to biodiversity and ecosystems, and they potentially cause economic problems and impact human health. The globally invasive New Guinea flatworm, Platydemus manokwari (Platyhelminthes: Geoplanidae), has been identified as a threat to terrestrial biodiversity, particularly soil-dwelling native species (e.g. molluscs, annelids and other land planarians), and is listed among 100 of the world's worst invasive alien species. We report here, for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…), and more recently to Europe, North America, and Asia (Chaisiri et al., 2018; Hu et al, 2019; Justine, Winsor, Gey, Gros, & Thévenot, 2014; Justine et al., 2015). This planarian has caused significant damage to native snail populations in some invaded areas (Iwai, Sugiura, & Chiba, 2010; Sugiura, 2009; Sugiura, Okochi, & Tamada, 2006), and has been recognized as a paratenic host for the nematode Angiostrongylus cantonensis (Chen, 1935), which causes angiostrongyliasis (Asato et al., 2004; Chaisiri et al., 2018). Despite not being in the blacklist, another planarian species, the ‘hammer‐head planarian’ Bipalium kewense Moseley, 1878 is one of the most popular invasive planarians, perhaps for being one of the species that has virtually ‘conquered the world’.…”
Section: Introductionmentioning
confidence: 99%
“…), and more recently to Europe, North America, and Asia (Chaisiri et al., 2018; Hu et al, 2019; Justine, Winsor, Gey, Gros, & Thévenot, 2014; Justine et al., 2015). This planarian has caused significant damage to native snail populations in some invaded areas (Iwai, Sugiura, & Chiba, 2010; Sugiura, 2009; Sugiura, Okochi, & Tamada, 2006), and has been recognized as a paratenic host for the nematode Angiostrongylus cantonensis (Chen, 1935), which causes angiostrongyliasis (Asato et al., 2004; Chaisiri et al., 2018). Despite not being in the blacklist, another planarian species, the ‘hammer‐head planarian’ Bipalium kewense Moseley, 1878 is one of the most popular invasive planarians, perhaps for being one of the species that has virtually ‘conquered the world’.…”
Section: Introductionmentioning
confidence: 99%
“…The land flatworm Platydemus manokwari is a highly invasive species, listed among the "100 World's Worst Invader Alien Species" (Lowe et al 2000). Originally described from a locality in Papua New Guinea (de Beauchamp 1962), it has been recorded since in many islands of the Pacific Ocean, Australia, and, more recently, in Porto Rico in the Antilles, Florida in mainland USA (Justine et al 2015;Justine et al 2014), and mainland Asia in Hong Kong (Hu et al 2019) and Thailand (Chaisiri et al 2019). We report here its presence in Guadeloupe, an island of the Caribbean arc.…”
Section: Introductionmentioning
confidence: 54%
“…Clearly, records from citizen science should be considered with this bias in mind. Cultural differences between urban and rural populations in France are probably relatively minor compared to what can be found in other countries; a recent study in Thailand found that more reports of P. manokwari were received from the great shore cities than from the inland (Chaisiri et al, 2019), which should be, in our opinion, interpreted more as a geographical/cultural bias, rather than a preferred location of the species.…”
Section: Geographical and Temporal Biases In Citizen Science Data: A mentioning
confidence: 66%
“…Many reports of new invasions by various species of land flatworms are published every year (Chaisiri et al, 2019;Hu et al, 2019;Jones, 2019;Justine et al, 2018aJustine et al, , 2019Prozorova & Ternovenko, 2018;Rodríguez-Cabrera & Torres, 2019;Soors et al, 2019; Week #21: Paper in PeerJ Figure 22 Reports of alien land planarians in 2018 in France (all species including Obama nungara), shown as weekly numbers. The total number of records in 2018 was 262.…”
Section: The Extent Of the Invasion In Metropolitan France And Europementioning
confidence: 99%